Entre baques e atraques : a inserção da medicina de família e comunidade na saúde suplementar - Oliveira, Isaac Linhares de (2023)
This master's thesis analyzes the training profile and performance of Family and Community Physicians inserted in the context of a Primary Health Care clinic that provides services to a health plan operator, in the city of Natal, Large northern river. It started from a cartographic study that took place between June/2021 and January/2022. The production of data took place through a closed electronic questionnaire, interviews and cartographic diaries. Of the eleven doctors who work at the clinic, nine answered the questionnaire and six carried out the interviews. One of them was also a researcher and contributed to the writing of cartographic diaries. The data were processed weekly with the research group, based on the theoretical references that support the article. With this, five analyzers were defined: "the encounter with social differences", "from training in the SUS to the enchantment with supplementary health", "the disenchantment and precariousness in supplementary health", "the dimension of the territory" and the " implication and over-implication in supplementary health research”. Three articles were produced from them. With this, it was observed that the option of action of these doctors in Supplementary Health is given by the approximation of their profile with the users of the clinic and by the better availability of soft-hard and hard technologies that help in the profession. On the other hand, this choice makes their work precarious, moving them away from the guarantee of basic labor rights and entails a loss of territorial dimension with weakening of the family and community approach.